PENGARUH KOMPETENSI DAN PENGAWASAN TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT. XYLO INDAH PRATAMA KABUPATEN MUSI RAWAS - Nasruddin Nasruddin; Wiwik Wahyuni (Jurnal Media Ekonomi (JURMEK), 2020)
This study aims to determine the effect of competence and supervision on employee work productivity at PT Xylo Indah Pratama, Musi Rawas Regency partially and simultaneously. The method used is a quantitative method. Questionnaire data collection techniques. The results of the research.Testing the first hypothesis to determine whether the competence of employee work productivity, the tcount value is 7,476 and the ttable is 1,292 (ttable value n = 77), so it can be seen that if the criteria match tcount> ttable then Ho is rejected and Ha is accepted. , meaning that there is an influence of competence on employee work productivity. The second hypothesis testing is to determine the effect of supervision on employee work productivity. The results obtained tcount value of 11.809 and ttable is 1.292 (ttable value n = 77) so it can be seen that if the criteria are in accordance with tcount> ttable then Ho is rejected and Ha is accepted, meaning that there is a supervisory effect on employee work productivity at PT Xylo Indah. Primary of Musi Rawas Regency. The third hypothesis is to determine the effect of competence and supervision on work productivity. Obtained the value of Fcount of 70,986 and Ftable of 3.12 This shows that Fcount> Ftable and also sig of 0.000 <0.05 so it can be seen that the effect is significant. Thus, it can be concluded that Ho is rejected and Ha is accepted. This means that there is an influence of competence and supervision on employee work productivity.